Pengembangan Komik Digital Berbasis Flipbook “Juzabi” pada Pembelajaran PAI Kelas IV SD - Ani Nur Aeni; Anisa Nur Fitriani; Frima Luthfi Lestari; Rihadatul Nasywa (Ta’dib : Jurnal Pendidikan Islam, 2025)
This study aims to develop and examine the feasibility of the digital comic “JUZABI” as a learning medium for Islamic Religious Education (PAI) in elementary schools to facilitate understanding in a more engaging and enjoyable way. The study employed the Design and Development (D&D) method with descriptive quantitative data analysis. Data were collected through questionnaires distributed to PAI teachers and fourth-grade elementary school students. The results indicate that the “JUZABI” digital comic is effective for use in learning, receives positive responses from students, and is deemed feasible by both subject-matter experts and media experts. Therefore, the “JUZABI” digital comic can serve as an alternative and attractive learning medium that helps improve the quality of instruction.